PERSEPSI PENYAKIT JANTUNG KORONER YANG AKANDILAKUKAN TINDAKAN KATETERISASI JANTUNG - Arif Hidayat; Erwin ' '; Ari Pristiana Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The purposeof thisstudywas to determine theperception ofcoronary heartdiseasepatientswhounderwent cardiac catheterizationwill. This research was conductedat RSUD Arifin AchmadPekanbaru. This research wasquantitativedescriptiveresearchdesign. The sampling methodwasconsekutifsamplingthe number ofrespondents30 people. Measuring instrument usedwas aquestionnairethathas beentestedcontentvaliditybycardiovascularexperts. The analysis usedwas aunivariateanalysis. The results showed thatthe majority ofrespondentsperceiveCHDsevere disease(83.3%), CHDdoes notrequireimmediate management(53.3%), cardiac catheterizationsurgerywithsurgery(66.7%), cardiac catheterizationactions thatrequirelongtreatment(63.3% ), cardiac catheterizationmildactionthatdoes nothave afatalrisk(63.3%), cardiac catheterizationis anact ofminimalrisk(66.7%), cardiac catheterizationtreatment measuresin total(60%), prior tocardiac catheterizationneed tochangelifestyle(56.7%),andcardiaccatheterizationactionwas an actionthat wasnotrepetitive(67%). The results ofthis study are expectedto be inputtothe relevant institutionsin particular RSUD Arifin Achmadpekanbaruthatimprovehealtheducationaboutheartcatheterizationsodo notperceivethatwrong. Keywords :cardiaccatheterization, coronaryheartdisease(CHD).